Analisis model kebijakan program penyaluran “KUR” dalam rangka meningkatkan perilaku kepatuhan wajib pajak pelaku “UMKM” - Widodo, Septrianto; Khusnaini; Widiatmanti, Herru (Directorate General of Taxes, 2024)
The Micro, Small, and Medium Enterprises (MSMEs) sector has long been a significant driver of Indonesia's economy, drawing considerable attention from the government. According to the National Medium-Term Development Plan (RPJMN), various strategic measures have been implemented to promote the growth and resilience of MSMEs as a means to enhance national economic independence. However, despite their substantial economic contribution, MSMEs' tax compliance remains low, as reflected in their minimal contribution to tax revenue. The small contribution is an indication that the level of compliance of MSMEs actors in fulfilling their tax obligations is still very low. This research was conducted using a qualitative approach and began by analyzing and evaluating the policy of the People's Business Credit (KUR) distribution program in relation to tax aspects. The analysis and evaluation were based on data sourced from literature studies and interviews with relevant resource persons from the point of view of technical feasibility, economic and financial possibility, political viability, and administrative operability. The results show that the existing policy has not fully accommodated taxation aspects. This is unfortunate considering that the KUR interest subsidy provided by the government to MSMEs actors is financed by the State Budget (APBN), which is mostly sourced from taxes. Furthermore, the study proposes policy model to encourage the development of the MSMEs actors.